The relationship of bone properties using high resolution peripheral quantitative computed tomography to radiographic components of hip osteoarthritis. Issue 9 (September 2017) - Edwards, M.H.; Paccou, J.; Ward, K.A.; Jameson, K.A.; Moss, C.; Woolston, J.; Javaid, M.K.; Cooper, C.; Dennison, E.M.
Summary: Objective: Positive associations between radiographic osteoarthritis (OA) and areal bone mineral density (BMD) have been demonstrated and appear strongest when bony features of OA are considered. To date, these associations have not been assessed using HRpQCT. Design: A total of 318 participants (170 men and 148 women), aged 72.1–81.4 years from a non-selected cohort, underwent HRpQCT of the distal radius and tibia along with hip radiography. Differences in bone microarchitecture were assessed between those with and without osteophytes, sclerosis or joint space narrowing (JSN) in either hip. Results: Men with osteophytes alone had significantly higher radial trabecular volumetric BMD (Tb.vBMD) and radial and tibial trabecular thickness (Tb.Th). Men with both sclerosis and osteophytes had significantly higher cortical volumetric BMD (Ct.vBMD) and cortical thickness (Ct.Th) at the distal tibia than those with osteophytes alone ( P < 0.05). These relationships were maintained after adjustment for age and Body Mass Index (BMI), and were not replicated in women. Bone microarchitecture did not differ significantly in those with JSN from those without it in men or women. Conclusions: Our findings suggest higher Tb.vBMD and Tb.Th in men with osteophytosis but higher tibial Ct.vBMD and Ct.Th in men with hip joint sclerosis. These results do however require replication in other cohorts.